Effectiveness of CADAS in Chatbot-Based Public Administration Services: Efektivitas CADAS dalam Pelayanan Administrasi Publik Berbasis Chatbot di Caturtunggal - Aprillia el- Qorina; Mei Maemunah (Universitas Indo Global Mandiri, 2026)
Purpose: This study analyzes the effectiveness of the Caturtunggal Digital System (CADAS) application in chatbot-based public administration services at Caturtunggal Village, Sleman. It also identifies user acceptance, supporting factors, and inhibiting factors in its implementation. Approach: This research used a descriptive qualitative approach. Data were collected through interviews, observation, and documentation involving one CADAS operator, one village official, one territorial administrator, and five community users. Data were analyzed through data condensation, data display, and conclusion drawing based on J. P. Campbell’s effectiveness indicators. Findings: CADAS is effective in supporting village-level public administration services. Its effectiveness is reflected in easier access through WhatsApp, faster information responses, reduced repetitive administrative work, clearer service procedures, and service availability beyond office hours. The main challenges are unequal digital literacy, limited chatbot interaction, and the need for continuous feature updates. Practical Implication: WhatsApp-based chatbot services can become a simple, low-cost, and accessible public service model for local governments. Originality: This study provides empirical insight into an AI-based WhatsApp chatbot at the village level and shows that service effectiveness is shaped by technology, accessibility, user habits, and administrative support.